Investigating the Link between Lynch Syndrome and Breast Cancer - Megan Sheehan; Brandie Heald; Courtney Yanda; Erinn Downs Kelly; Stephen Grobmyer; Charis Eng; Matthew Kalady; Holly Pederson (European Journal of Breast Health, 2020)

(untitled)
Objective:Lynch syndrome is an inherited genetic disorder associated with a predisposition to early-onset colorectal and endometrial cancers, but breast cancer risk in these patients is debated. The aim of this study is to evaluate breast cancer rates in a cohort of Lynch syndrome patients, as well as to identify women who may be eligible for additional breast cancer specific genetic testing or enhanced breast surveillance (contrast-enhanced magnetic resonance imaging (MRI) screening).Materials and Methods:Using a hereditary colorectal cancer registry at a single academic institution for identification of patients with Lynch syndrome, a retrospective chart review was performed of 188 women with DNA mismatch repair (MMR) mutations. The Tyrer-Cuzick model was used to estimate breast cancer risk in patients without breast cancer.Results:The prevalence of breast cancer differed based on mutation type (p=0.0043), as 27% of women with a PMS2 mutation were diagnosed with breast cancer, compared to 3%, 4%, and 9% in MLH1, MSH2, and MSH6 patients. The average age at diagnosis for women with a PMS2 mutation was 46.7 years. Additionally, 7.5% of unaffected women had an estimated lifetime risk of breast cancer greater than 20%. 46/188 (24.4%) of patients were eligible for breast specific genetic testing.Conclusion:Our analysis suggests that Lynch syndrome patients with PMS2 mutations may be at higher risk of developing breast cancer. Additionally, the personal and family history of cancer suggests crossover in eligibility for breast specific genetic testing in a significant number of patients (16.5-24.4%). Also, many women are eligible for enhanced breast surveillance (7.5%) which would otherwise not be offered.